2013
DOI: 10.1007/s10797-013-9283-y
|View full text |Cite
|
Sign up to set email alerts
|

The rise in female employment and the role of tax incentives. An empirical analysis of the Swedish individual tax reform of 1971

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 23 publications
4
32
3
1
Order By: Relevance
“…Our central estimate of 0.13 is well below the participation elasticities of married Swedish women estimated by Selin (2014). Selin exploited the 1971 Swedish tax reform which implied a switch from joint to individual taxation and found estimates in the range 0.5-1.0.…”
Section: Discussioncontrasting
confidence: 64%
“…Our central estimate of 0.13 is well below the participation elasticities of married Swedish women estimated by Selin (2014). Selin exploited the 1971 Swedish tax reform which implied a switch from joint to individual taxation and found estimates in the range 0.5-1.0.…”
Section: Discussioncontrasting
confidence: 64%
“…We also 22 See Bastani et al (2016) for further discussion about the relationship between the participation elasticity and the employment level. 23 The estimates reported by Selin (2014) and Bastani et al (2016) may at first glance seem very different. They are however consistent if one notices that Selin (2014) reports that the pre-reform share of married women with positive earnings was 67% (Table 8) whereas the corresponding share in Bastani et al (2016) is 90%.…”
Section: Resultsmentioning
confidence: 94%
“…23 The estimates reported by Selin (2014) and Bastani et al (2016) may at first glance seem very different. They are however consistent if one notices that Selin (2014) reports that the pre-reform share of married women with positive earnings was 67% (Table 8) whereas the corresponding share in Bastani et al (2016) is 90%. 24 See Swedish Ministry of Finance (1989), supplement 4, p. 15. report how the government's relative valuation of working and non-working individuals has changed over time.…”
Section: Resultsmentioning
confidence: 94%
“…The introduction of the individual tax system in 1971, whereby taxation of spouses was individualized, also created big incentives for women to participate in the labour force. Selin (2014) concluded that the labour supply of females increased by 10 percentage points because of this reform.…”
Section: Reasons For High Female Labour Supply In Swedenmentioning
confidence: 99%